Change Management and Organizational Performance: A Bibliometric Analysis of Scopus-Indexed Literature - Wati, Erna; Wandik, Kandius; Aseanty, Deasy; Anggiani, Sarfilianty (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Change management has emerged as a critical factor in enhancing organizational performance in today’s rapidly evolving business environment. Although extensive research has examined this relationship, existing literature remains fragmented across disciplines, lacking a cohesive understanding of its intellectual structure and thematic evolution. This study employs a bibliometric review of recent Scopus-indexed publications to systematically analyze trends, influential authors and institutions, key research themes, and collaboration patterns in the field. Using PRISMA (Preferred Reporting Items for Systematic Reviews) method, the review aims to uncover how change management practices—particularly those involving digital transformation, agile strategies, and leadership engagement—are associated with performance outcomes. The analysis is expected to reveal dominant research clusters, evolving keywords, and increasing scholarly attention to technology-driven and human-centered change approaches. By synthesizing a decade of research, this study contributes to the academic literature by offering a structured overview of the field’s development and highlighting gaps for future investigation. It also provides practical insights for organizations seeking to implement effective change initiatives aligned with strategic performance goals. The findings will support scholars in identifying future research directions and assist practitioners in applying evidence-based change management strategies across diverse organizational contexts.